PENGARUH METODE EKSPERIMEN TERHADAP HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 14 SINGKAWANG - Elni Evifania Dova; Eka Murani; Buyung (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to: (1) determine the effect of the experimental method on the science learning outcomes of fifth-grade elementary school students, and (2) measure the extent of its influence on the material of magnetic force. This research employed an experimental method with a quantitative approach and a one-group pretest-posttest design. The study was conducted at SDN 14 Singkawang with a sample of 23 fifth-grade students. Data collection used test instruments in the form of multiple-choice questions. The results show that: (1) the normality test for pretest scores yielded a significance value of 0.077 (> 0.05) and for posttest scores 0.071 (> 0.05), indicating that both datasets are normally distributed; (2) the homogeneity test produced a significance value of 0.206 (> 0.05), indicating homogeneous data; (3) the paired sample t-test yielded tcount = 6.14 and ttable = 2.01, so tcount > ttable (6.14 > 2.01), meaning Hₐ is accepted and H₀ is rejected; (4) the effect size was calculated at 1.543, which falls into the high category. These findings conclude that the experimental method significantly improves science learning outcomes for fifth-grade students at SDN 14 Singkawang on the topic of magnetic force. The method effectively enhances students’ understanding by engaging them in direct observation, experimentation, and analysis, which supports active learning and develops scientific process skills. Teachers are recommended to apply the experimental method in science lessons to increase both achievement and engagement.